Identify Factors to Minimize Ruin Probability in Insurance Industry - Ami Ludin, Nurul Hidayah; 2Prof Madya Dr. Kavikumar S/O Jacob (Enhanced Knowledge in Sciences and Technology, 2022)
The level of an insurer’s excess for a portfolio of insurance policies is the subject of ruin theory. The purpose of this research is to investigate the factors to minimize the probability of ruin in insurance industry by reinsurance. Then, study the process of reinsurance in the insurance environment. The problem is solved using Microsoft Excel and Matlab.